(untitled) (Acta Scientiarum. Agronomy, 2025)
The evaluation of Corymbia maculata and C. torelliana progenies has received much attention in Brazil in the last decade. For the process to be efficient, experiments must be as precise as possible. Factors that affect accuracy include plant survival (PS) and assessment age. The objectives of this study were to determine whether there are differences in progeny PS among evaluation sites and ages, whether dominated plants affect precision estimates, and how potential damage caused by differences in PS can be mitigated. Data from the evaluation of half-sib progenies of C. maculata at three sites and C. torelliana at four sites were used. The experiments were implemented in an alpha-lattice design with 40 repetitions and a single-tree plot (STP). Diameter at breast height (DBH) and PS data were obtained at three and six years of age. All plants that presented DBH with a deviation below the mean (dominated plants) were not considered in the survival estimates. Although there was a difference in plant survival between progenies and experiments, none of the strategies used to mitigate damage due to differences in PS significantly changed the classification of progenies or the magnitude of the accuracy. There was a high association between the estimates obtained at three and six years of age, indicating that for species of the genus Corymbia, early selection is viable.